Information asymmetry, capital structure and equity value of firms listed on the WSE - Milena Gralewska; Anna Białek-Jaworska (Journal of Banking and Financial Economics (JBFE), 2022)
The paper investigates the impact of capital structure and information asymmetry on the value of companies listed on the Warsaw Stock Exchange. The study was conducted using the ordinary least squares (OLS) method on a sample of 273 companies in 2017 and the GMM dynamic paneldata approach with instrumental variables. Data retrieved from the Notoria, Bloomberg and Orbis databases were used. The results show that despite its impact on reducing the cost of capital, increasing debt does not lead to an increase in equity value. Therefore, the benefi ts of higher short-term leverage are limited and visible only for long-term debt. On the other hand, despite bigger information asymmetry, companies are valued higher, which means that asymmetrical information does not necessarily hurt valuation in the short term but in the long term. The results contribute to the literature on firms' use of leverage under information asymmetry, showing higher trust in cash flow than profits in books.
Keywords: A1; B2; C5; G1; G2; G3; 330; information asymmetry; capital structure; market value of the company; WACC